A descriptive study on dental implant perceptions among partially edentulous patients from social strata C in the City of Manila - De Jesus, Marie Angeline O.; Utlang, Joan Ishtar R.; Mendoza, Michael Antonio F. (Adviser).
Most studies on dental implants suggest that they promise aesthetic, biomechanical, and clinical benefits. Several studies prove of its high success rates. However, not all potential patients know or are aware of these benefits. A variety of factors affects the decision on the selection of a treatment option that a partially edentulous patient makes. These include the cost of the treatment, patient awareness on the different treatment options, and fear and anxiety of surgical procedures. Patient awareness on implants is influenced by informational ads, people around him/her, and journals and articles. This study aimed to determine the perception of partially edentulous patients within the Socio-Economic Classifications C in the City of Manila on dental implants. The researchers conducted a survey using self-administered questionnaires as a means of gathering data. The study focused on patient perception regarding price, awareness of availability of dental implants in the City of Manila, expectations and concerns regarding dental implant treatment. From the results of the study, it can be concluded that partially edentulous patients (66.88% of the 154 respondents) within the socio-economic classifications C in the City of Manila have knowledge on what a dental implant is. The results are the same for all the different age groups and both genders. Their primary concern is esthetics (35.30% of the higher age group and 28.08% of the female respondents) and they expect dental implants to be costly (a mean of 70.87%). Subjects who did not consider dental implants as a treatment option think that dental implants are expensive and painful. Male and female subjects from the lower (78.33%) and middle age groups (70%) would consider dental implants as a treatment option.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dental implants